Analisis Kebutuhan Ruang Terbuka Hijau Publik dan Privat dengan Memanfaatkan Penginderaan Jauh di Kecamatan Padang Utara - Desra Ramawati Syahputri; Heny Mariati; Novelisa Suryani (Jurnal Pembangunan Nagari, 2023)
Many built-up areas will occur in the near future causing development growth to develop rapidly. So that it is necessary to analyze the needs of public and private green open space in the District of North Padang. The purpose of this study was to determine the distribution of public and private green open space in the District of North Padang and to analyze the great need for public and private green open space in the district of North Padang. Using quantitative descriptive research methods and remote sensing in the form of CSRT data. The results of this study indicate that the area of ​​public green open space in North Padang District is 37,941 ha. Meanwhile, the area of ​​private green open space in North Padang District is 94,394 ha. The distribution of public and private green open space in Padang Utara District is evenly distributed. The need for green open space in North Padang District is 161.6 ha of public green open space and 80.5 ha of private green open space from the total area of ​​North Padang District. For the government and the people of North Padang District, if they want to add green open space, it is best to close the shortage of public green open space of around 109,765 ha. In this way, the problem of public green open space has found a solution to complement the previous deficiencies, and public green open space has complied with Minister of Public Works Regulation No.05/PRT/M/2008.